Who says who interprets? On the possible existence of an interpreter system. (3rd April 2022) - Pym, Anthony
ABSTRACT: If we ask who is selected to interpret in a particular setting, who is most trusted, the answers rarely concern interpreting as an independent social system. Different legal systems decide whom they trust as translators; institutional employers carry out their own exams; education systems provide signals of competence; the systems of controlled knowledge (science) and its diffusion (news) tend to rely on their own members who 'know languages' and, as has been seen in the case of pandemic-related information, rarely display constant trust in wholly independent interpreters. Analysis of interpreters' trustworthiness in terms of Luhmann's sociology can thus start from dependencies between at least four possible types of system: interpreters supply utterance; legal systems assume truthful utterance; education systems attest the relative trustworthiness of utterance; systems of knowledge control and diffusion (science, the military, government information, news) assume shared skills or ad hoc modes of professional hybridity. On this view, an interpreter system is only sometimes able to create its own signals of trustworthiness and have those signals accepted. In many instances, it must rely on intersystemic relations, which are often irritations ensuing from the way one social system is given to not understanding another.